2015
DOI: 10.1007/s40256-014-0104-1
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Dysrhythmias Associated with Poisoning and Drug Overdose: A 10-Year Review of Statewide Poison Control Center Data from California

Abstract: Key PointsThe most commonly involved therapeutic classes of drugs associated with ventricular fibrillation and/or tachycardia (VT/VF) were antidepressants (25 %) and stimulants (25 %).The drugs most commonly associated with torsade de pointes (TdP) were antidepressants (25 %) and methadone (25 %).Drug exposures with the greatest risk of death in association with VT/VF were antidepressant exposure [odds ratio (OR) 1.71] and antiarrhythmic exposure (OR 1.75), but neither association was statistically significant. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Ventricular arrhythmias, especially torsades de pointes, are feared consequences of QT prolongation and may be the cause of death in some poisonings. 38 39 However, as torsades de pointes is a rare condition, 38 39 it is unlikely to have influenced our results.…”
Section: Discussionmentioning
confidence: 83%
“…Ventricular arrhythmias, especially torsades de pointes, are feared consequences of QT prolongation and may be the cause of death in some poisonings. 38 39 However, as torsades de pointes is a rare condition, 38 39 it is unlikely to have influenced our results.…”
Section: Discussionmentioning
confidence: 83%
“…First, due to the deidentified nature of the data, we were not able ascertain cardiac death, but given the small number of severe cardiac events, we expect the number of cases to be negligible. Second, we were not able to capture use of proarrhythmic over‐the‐counter medications, such as pseudoephedrine and diphenhydramine . The use of such products is likely during active infections to manage cough and cold symptoms while patients are exposed to study antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Diphenhydramine has been associated with (1) TdP, occasionally during voluntary overdoses [4446]; (2) a strong signal for TdP in the databases from drug regulatory agencies [47]; (3) QTc prolongations during voluntary overdoses [4852], and (4) QTc prolongations in EKGs completed at the emergency room when prescribed by itself or with other drugs that prolong the QTc interval [53]. However, some of these diphenhydramine overdose studies with EKG data, including 126 cases of overdoses with no TdP case [48] and 1 case monitored for several days [50], suggested that diphenhydramine causes tachycardia and this has a major effect on protecting from TdP in situations of QTc prolongation.…”
Section: Discussionmentioning
confidence: 99%